2003
DOI: 10.2165/00128072-200305010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Children and Adolescents with Cystic Fibrosis

Abstract: Health related quality of life (QOL) as an outcome measure in clinical trials is becoming increasingly important. Trials should not only be able to demonstrate the pharmacologic activity of a therapy, but of equal importance, they should demonstrate clinical effectiveness that is of significant benefit to the patient. QOL measurement provides a way of incorporating the child/parent's perspective of how cystic fibrosis (CF) and its therapies impact on their lives. Several validated generic instruments have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 112 publications
(105 reference statements)
1
10
0
Order By: Relevance
“…Quittner et al reported similar findings in observable dimensions in a large, multicentre, cohort study in the United States [25]. Previous publications identified the opposite trend between patient- and parent-proxy report [6,29]. In the present study, Respiratory symptoms were associated with lower HRQoL scores in CF patients; this is consistent with the findings of Szyndler et al [30].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Quittner et al reported similar findings in observable dimensions in a large, multicentre, cohort study in the United States [25]. Previous publications identified the opposite trend between patient- and parent-proxy report [6,29]. In the present study, Respiratory symptoms were associated with lower HRQoL scores in CF patients; this is consistent with the findings of Szyndler et al [30].…”
Section: Discussionsupporting
confidence: 91%
“…Although parents know their children, they may not have insight into the child’s feelings and thoughts, which could explain their differing perspectives on the factors that influence HRQoL most. Additionally, children may not wish to discuss the true impact of CF on their lives, to avoid distressing their parents [6]. Consequently it is necessary to obtain information about HRQoL from both the child and his or her caregivers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1998; Levi & Drotar 1999; Britto et al . 2000; Eiser & Morse 2001; Abbott & Gee 2003; Sturms et al . 2003).…”
Section: Introductionmentioning
confidence: 99%
“…2003). However, there are strong arguments for obtaining information from both parents and children whenever possible (Eiser & Morse 2001; Abbott & Gee 2003), for example, to determine similarities and mismatches in the perception of the child and parent or to appreciate some of the complex family dynamics (Abbot & Gee 2003). In addition, it is important to look at the differences in HRQOL reports between parents and children in order to direct appropriate interventions if necessary (Henry et al .…”
Section: Introductionmentioning
confidence: 99%